Konsep “Merdeka Belajar” dalam Pandangan Filsafat Konstruktivisme - M. Yusuf; Witrialail Arfiansyah (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2021)
This paper tries to understand the "Merdeka Belajar" policy program launched by the Ministry of Education and Culture of the Republic of Indonesia in the light of constructivism philosophy. Constructivism is a philosophi that assumes that knowledge is self-construction. Because the nature and learning outcomes are subjective, and depend on each individual, also uncertain, for one's constructivism entity and are more easily recognized by the term "Clutter Paradigm". There are parallels between what was proclaimed by Mas Minister Nadiem Makarim and the concept of education according to the philosophy of the concept of constructivism. Both of them emphasize the aspects of freedom, independence, and flexibility of educational institutions in understanding the competence of students. Learning arrangement with a chaotic approach so that students can be safe, comfortable, and easy to learn. Students as learning subjects –learner control play an important role in structuring the learning. The initiative of children as learners to learn –the willingness to learn- will die when faced with many rules that do not exist in the learning process. It takes freedom, reality, as well as positive attitudes and perceptions of learning as basic capital in the danger of learning initiatives that ultimately result in success in learning.